2018
DOI: 10.1016/j.alit.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cha o 3 homolog Cry j 4 from Cryptomeria japonica (Japanese cedar) pollen: Limitation of the present Japanese cedar–specific ASIT

Abstract: Cry j 4 was discovered as a counterpart allergen of Cha o 3 in Japanese cedar pollen, with a relationship similar to that between Cry j 1-Cha o 1 and Cry j 2-Cha o 2. Our findings also suggest that allergen-specific immunotherapy (ASIT) using Japanese cedar pollen extract does not induce adequate immune tolerance to Cha o 3 due to the low amount of Cry j 4 in Japanese cedar pollen. Therefore, ASIT using Cha o 3 or cypress pollen extract coupled with Japanese cedar pollen extract is required in order to optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“… 6 In their subsequent studies, 13 of 14 (92.9%) and 18 of 18 (100%) patients with JCy pollinosis were BAT-positive to Cha o 3. 7 , 8 In addition, PBMCs from patients with JCy pollinosis produced significant IL-5 after Cha o 3 stimulation. 8 Thus, on the basis of the findings of these studies, Cha o 3 appears to be a major allergen in JCy pollinosis.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“… 6 In their subsequent studies, 13 of 14 (92.9%) and 18 of 18 (100%) patients with JCy pollinosis were BAT-positive to Cha o 3. 7 , 8 In addition, PBMCs from patients with JCy pollinosis produced significant IL-5 after Cha o 3 stimulation. 8 Thus, on the basis of the findings of these studies, Cha o 3 appears to be a major allergen in JCy pollinosis.…”
Section: Resultsmentioning
confidence: 94%
“…The current findings of the BAT and the JCy-specific IgE suppression test are in striking contrast to the findings of previous reports. 6 , 7 , 8 In their original study, Osada et al showed that 87.5% of patients with JCy pollinosis were positive for Cha o 3–specific IgE and 3 of 3 patients with JCy pollinosis showed positive basophil activation in response to Cha o 3 to the same or even higher extent than to Cha o 1. 6 In their subsequent studies, 13 of 14 (92.9%) and 18 of 18 (100%) patients with JCy pollinosis were BAT-positive to Cha o 3.…”
Section: Resultsmentioning
confidence: 99%
“…Cry j 2, the second allergen isolated from JC PE, is a protein with a Mw of 37-45 kDa and is a homolog of polygalacturonase. New allergens from JC PE have been reported, such as Cry j 3 and Cry j 4 [15,16]; however, allergens Cry j 1 and Cry j 2 still affect the largest proportion (more than 95%) of JCP patients [17].…”
Section: Cry J Allergens and Pementioning
confidence: 99%
“…According to earlier research, pollen and aeroallergens are accountable for over 92% and almost 63% of allergic rhinitis cases, respectively [34,36,37]. Four allergens (Cry j 1, Cry j 1, Cry j 3, and Cry j 4) have been isolated from JC pollen so far [38][39][40]. Cry j 1, the first predominant allergen recognized in JC pollen, is homologous to pectate lyase and appears on the small particles on the pollen surface and the outer wall [38,[41][42][43].…”
Section: Introductionmentioning
confidence: 99%